Gender roles in ruminant disease management in Uganda: Implications for the control of peste des petits ruminants and Rift Valley fever - Namatovu, Jane; Lule, Peter; Asindu, Marsy; Campbell, Zoë A.; Tumusiime, Dan; Kiara, Henry K.; Bett, Bernard K.; Roesel, Kristina; Ouma, Emily A. (2025)
There is a distinct division of tasks and roles between men and women in livestock management in the different ruminant production systems in Uganda. Division of roles can influence disease control and prevention. This qualitative study asks what men and women do to prevent or control diseases that affect them and their livestock and what factors influence the choice of disease control measures taken. Discussants represented three production systems (pastoral, agro-pastoral, and mixed crop livestock), selected for the high prevalence of two livestock diseases (peste des petits ruminants and Rift Valley fever). Sex-disaggregated focus group discussions with livestock keepers and key informant interviews with veterinarians and other experts were conducted in six districts in the western, northeastern, and eastern regions of Uganda. Gendered livestock management roles strategically positioned men, women, girls, and boys to observe different clinical manifestations of disease. Livestock keepers mostly reported within-farm prevention and control methods, for which they presumably had more control than between-farm or community-level methods. While livestock keepers embraced disease control options such as the use of drugs, spraying acaracides, and the use of traditional herbs, many had concerns and misconceptions about vaccination as a preventive measure. Although women had fewer concerns about vaccine side effects, they still faced constraints, such as mistrust of animal health workers, limited decision-making powers, domestic workload, and inability to access vaccination points. The study findings can guide appropriate, gender-responsive interventions tailored by production system for controlling ruminant diseases in Uganda.